Focus: Music of South Africa, by Carol A. Muller, 2nd ed., Routledge, New York 2008 (1st ed. 2004), Focus on World Music Series, edited by Michael B. Bakan, 338 pp., 56 photographs, with audio CD. - Tracey, Andrew (International Library of African Music, 2009)
pages: 163
Keywords: South Africa; African Music